2009
DOI: 10.1111/j.1600-0668.2009.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental characteristics and climatic factors on mites in the dust of air-conditioner filters

Abstract: Mites present in the dust of air-conditioner filters are potential indoor threat to asthma and allergy sufferers. In this study, we find that the storage mite Tarsonemus granarius is the predominant species of mites in the dust of air-conditioner filters (MACF). Thus, the possible clinical importance of T. granarius should cause more our attentions in the future. The abundance and distribution of MACF are also found significantly varied in different climatic regions of China. When we try to assess the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This may be attributed to Guangzhou's tropical climate, whose warm and humid environment facilitated the growth and proliferation of HDMs. Previous local surveys have found the concentration of HDMs to be high in Guangzhou families , especially in rooms equipped with air conditioners . In the current survey, the concentration of HDMs was also measured at relatively high level (median = 1.6 μg/m 2 ) in bed .…”
Section: Discussionsupporting
confidence: 48%
“…This may be attributed to Guangzhou's tropical climate, whose warm and humid environment facilitated the growth and proliferation of HDMs. Previous local surveys have found the concentration of HDMs to be high in Guangzhou families , especially in rooms equipped with air conditioners . In the current survey, the concentration of HDMs was also measured at relatively high level (median = 1.6 μg/m 2 ) in bed .…”
Section: Discussionsupporting
confidence: 48%
“…Indoor HDM level has been found to be higher from beds and in most of the families with installation of air‐conditioners. The filters of these air‐conditioners have been found to contain a high concentration of HDM . Thus, exposure to mite in household dust or from air‐conditioner filters and beds may be an important risk factor for the development of sensitizations and allergic airway diseases in Guangzhou.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a study on measuring levels of mite allergens from beds in Guangzhou where we found 88% of dust samples from mattresses showed levels of Der1 above 10 μg/g. 21 Wu et al 22 collected dust from air-conditioner filters from six cities of China and found D. pteronyssinus and D. farinae in the filters. Cui and Wang performed a study in Huainan city of Anhui province of China and also suggested that mite occurrence rate on the surface of air-conditioner filters was high 23 While the air conditioner is running, mite allergens accumulated in the dust of filters and the settled dust can be continuously whirled into indoor air and raise the allergy risk for patients with asthma and rhinitis living in the room.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a study on measuring levels of mite allergens from beds in Guangzhou where we found 88% of dust samples from mattresses showed levels of Der1 above 10 g/g. 21 Wu et al 22 collected dust from air-conditioner filters from six cities of China and found D. pteronyssinus and D. farinae in the filters. Cui and Wang performed a study in Huainan city of Anhui province of China and also suggested that mite occurrence rate on the surface of air-conditioner filters was high.…”
Section: Discussionmentioning
confidence: 99%